K-House: Linguistic-Cultural Synergy among Online Filipino Communities - Palileo, Shirley (Social Sciences and Development Review, 2024)
This ethnographic study examines the significance of linguistic cultural hybridity among online Filipino communities watching Korean drama series. The study demonstrates the interwoven deeds of online Filipino communities in terms of language, performative acts, and habituation interdependent with the residents’ literacy, nature, and environment. Using the generated Inter Phenomenon Linguistic Cultural (IPLC) model, the study appraises the apparent discourses in K-dramas, assesses the residents’ K-drama-related performatives, and underscores the processes of habituation in platforms connected to conversations and meaning-making with others. These findings and processes endorse the principles, praxes, technology, history, and referentiality of language of online Filipino communities that are collectively rooted in their understanding and environment. By extension, the study sustains and empowers glocalized syncretism, cultural synergy, and transculturation.